Mitofusin gain and loss of function drive pathogenesis in Drosophila models of CMT2A neuropathy. (13th June 2018) - El Fissi, Najla; Rojo, Manuel; Aouane, Aїcha; Karatas, Esra; Poliacikova, Gabriela; David, Claudine; Royet, Julien; Rival, Thomas
Abstract: Charcot–Marie–Tooth disease type 2A (CMT2A) is caused by dominant alleles of the mitochondrial pro‐fusion factor Mitofusin 2 (MFN2). To address the consequences of these mutations on mitofusin activity and neuronal function, we generate Drosophila models expressing in neurons the two most frequent substitutions (R94Q and R364W, the latter never studied before) and two others localizing to similar domains (T105M and L76P). All alleles trigger locomotor deficits associated with mitochondrial depletion at neuromuscular junctions, decreased oxidative metabolism and increased mtDNA mutations, but they differently alter mitochondrial morphology and organization. Substitutions near or within the GTPase domain (R94Q, T105M) result in loss of function and provoke aggregation of unfused mitochondria. In contrast, mutations within helix bundle 1 (R364W, L76P) enhance mitochondrial fusion, as demonstrated by the rescue of mitochondrial alterations and locomotor deficits by over‐expression of the fission factor DRP1. In conclusion, we show that both dominant negative and dominant active forms of mitofusin can cause CMT2A‐associated defects and propose for the first time that excessive mitochondrial fusion drives CMT2A pathogenesis in a large number of patients. Synopsis: In vivo expression in Drosophila motor neurons reveals that the two most prevalent forms of mitofusin alleles associated with CMT2A neuropathy (R94Q and R364W) have opposite effects on mitochondrial fusion. Mutations near/within the GTP‐binding domain of mitofusin (R94Q and T105M) inhibit fusion and trigger aggregation. Mutations within Helix‐Bundle 1 (R364W and L76P) enhance mitochondrial fusion. Aggregation and excess fusion both impact on mitochondrial distribution and turn over and induce locomotor defects in Drosophila . Abstract : In vivo expression in Drosophila motor neurons reveals that the two most prevalent forms of mitofusin alleles associated with CMT2A neuropathy (R94Q and R364W) have opposite effects on mitochondrial fusion.